The magicians. Season three [videorecording (DVD)] - Ralph, Jason, 1986-; Appleman, Hale, 1986-; Maeve, Stella; Grossman, Lev (Universal, 2018)
The hit series based on Lev Grossman's best-selling novels returns for season three as Quentin Coldwater and his magician friends now face a world without magic. Deprived of their special powers, Quentin and the other magicians are desperate to find a way to restore magic. But in order to regain what has been lost, they must embark on an epic quest that cannot be accomplished alone. Now more than, ever, our heroes must rely on one another.